Hubungan Supervisi Kepala Ruangan Dengan Pengelolaan Sampah Medis Oleh Perawat Di Ruangan Rawat Inap - anugrahmureski anugrah (Jurnal Medika Hutama, 2021)
Medical waste, such as: needles, diagnostic samples, blood, drugs, health care equipment, and radioactive materials is generated from health care activities.. The research aims to determine the correlation between supervision by room leader and medical waste treatment by nurses stationed at inpatient room. It is a quantitative study using descriptive correlative design with cross sectional approach. The total sample for this study is 49 individuals chosen by purposive sampling technique. Data analysis was done by both univariate and bivariate. The univariate analysis was done using frequency distribution, while the bivariate using chi square. The result shows that 29 respondents were female of early adulthood (59.2%). 32 respondents (65.3%) were female, and 32 respondents (65.3%) were 3-year diploma graduates, which is the highest of all other graduates. In addition, 38 respondents (77.6%) have been working for more than 6 years. 26 respondents stated that supervision by their room leader was in accordance to the basic principles, and 25 respondents (51%) conducted proper medical waste treatment. The result showed that Pvalue 0.001 (<0.05), wich means there was a valuable correlation between supervision by room leader and medical waste treatment by nurses stations and inpatient room. The result of chi square test showed that Pvalue 0.000 (<0.05), which means that there was a valuable between supervision by room leader and medical waste containment by nurses. The result of chi square test with Pvalue 0.266 (> 0.05), show ed that there was no valuable between supervision by room leader and medical waste sorting by nurses. It is hoped that room leaders in hospitals can improve their supervision, particularly in term of observation, so that it can improve the performance of stationed nurses in sorting and containment process of medical waste. Keywords : Room Leader, Medical Waste Treatment, Nurse, Supervision